Tumor immunity is related to 18F‐FDG uptake in thymic epithelial tumor. (7th August 2021) - Imai, Hisao; Kaira, Kyoichi; Hashimoto, Kosuke; Nitanda, Hiroyuki; Taguchi, Ryo; Yanagihara, Akitoshi; Umesaki, Tetsuya; Yamaguchi, Ou; Mouri, Atsuto; Kawasaki, Tomonori; Yasuda, Masanori; Kobayashi, Kunihiko; et al.
Abstract: Background: 2‐deoxy‐2‐[fluorine‐18] fluoro‐d‐glucose ( 18 F‐FDG) positron emission tomography ( 18 F‐FDG‐PET) is a convenient modality to assess the metabolic activity within tumor cells. However, there is no consensus regarding the relationship between 18 F‐FDG uptake and the immune environment in thymic epithelial tumors (TETs). We conducted a clinicopathological study to elucidate the relationship between 18 F‐FDG uptake and programmed death ligands 1 and 2 (PD‐L1/PD‐L2) expression in patients with TETs. Methods: A total of 108 patients with histologically confirmed TETs classified as thymomas or thymic carcinomas who underwent surgical resection or biopsy or needle biopsy and 18 F‐FDG PET before any treatment between August 2007 and March 2020 were enrolled in this study. Tumor specimens underwent immunohistochemical staining for PD‐L1, PD‐L2, GLUT1, HIF‐1α, VEGFR2, VEGF‐C, and β2 adrenergic receptor. Results: High uptakes of SUVmax, SUVmean, MTV, and TLG were identified in 28 (25.9%), 61 (56.5%), 55 (50.9%), and 55 (50.9%) of 108 patients, respectively. High uptake of SUVmax significantly correlated with PS (performance status) of 1–2, thymic carcinoma, and advanced stage, and SUVmax on 18 F‐FDG uptake displayed a close association with PD‐L1 and PD‐L2 expressions, but not with MTV and TLG. Our analysis revealed that SUVmax was identified as being significant relationship for positive PD‐L1/PD‐L2 expression. GLUT1, HIF‐1α, and VEGFR2 were significantly associated with the expression of PD‐L1/PD‐L2 from the biological viewpoint. Conclusion: 18 F‐FDG accumulation was closely associated with the expression of PD‐L1/PD‐L2, which, in turn, was correlated with glucose metabolism and hypoxia. PD‐L1/PD‐L2 could affect the glucose metabolism and hypoxia in thymic tumor cells. Abstract : High expression of PD‐L1/PD‐L2 was closely associated with high accumulation of 18F‐FDG.　Angiogenetic markers were linked to the expression of PD‐L1/PD‐L2.　PD‐L1 and PD‐L2 exhibited a close relationship with upregulation of tumor glucose metabolism and hypoxia.